The dual role of Piezo1 in tumor cells and immune cells: a new target for cancer therapy - Qu, Peng; Zhang, Hongyan (Frontiers in Immunology, 2025)
Piezo1, a mechanosensitive ion channel, plays a pivotal and multifaceted role in tumor progression, immune evasion, and therapeutic resistance by transducing extracellular mechanical stimuli—such as matrix stiffness and fluid shear stress—into intracellular calcium influx. In tumor cells, Piezo1 promotes proliferation, invasion, and metastasis by activating oncogenic signaling and contributes to an immunosuppressive TME through regulation of cancer-associated fibroblasts (CAFs) and extracellular matrix (ECM) remodeling. In the immune compartment, Piezo1 integrates mechanical cues with metabolic and epigenetic reprogramming to orchestrate the functions of T cells, macrophages, and natural killer (NK) cells. Notably, Piezo1 deficiency impairs TH9 cell differentiation, diminishes T cell cytotoxicity, and enhances the activity of regulatory T cells (Tregs). Furthermore, Piezo1 expression correlates with distinct tumor immune phenotypes, such as “cold tumors,” and with responses to immunotherapy, making it a promising predictive biomarker for treatment efficacy. Given its dual regulatory roles in tumor biology and immune modulation, targeting Piezo1—such as through combination with programmed death-1 (PD-1) blockade—offers a potential strategy to reverse immunosuppression and enhance antitumor immunity. This review summarizes emerging insights into Piezo1’s role in cancer progression and immune regulation and highlights its translational potential as a novel target in cancer immunotherapy.